Effect of oyster mushroom (Pleurotus sajor-caju) addition on the nutritional composition and sensory evaluation of herbal seasoning - Saiful, B.S.; Wan Rosli, W. I. (Universiti Putra Malaysia, 2016)
The present study was conducted to investigate the effect of oyster mushroom (Pleurotus sajorcaju, PSC) addition to partially replace coconut milk powder on nutritional composition and sensory values of Herbal Seasoning (HS). This study evaluates the nutritional composition, dietary fibre and sensory acceptance of HS that processed using six different formulations with different levels of PSC powder, namely 0% (A), 20% (B), 40% (C), 60% (D), 80% (E) and 100% (F). The use of PSC powder substantially brought down the fat content of HS. The fat content of PSC-based HS was ranged from 13.82±0.84% to 8.16±0.74%. The protein content showed an increasing trend in line with increasing of PSC powder ranging from 7% to 12%.Substitution of coconut milk powder with PSC powder resulted in significantly higher (p<0.05) of total dietary fibre content (TDF). The TDF content was ranging from 15.53% to 22.02%. The sensory evaluation showed that both HS contained 100% and control were not significant different (p>0.05).The panels preferred HS formulated with PSC powder since its enhance colour and viscosity attributes of the products. In brief, HS formulated with more than 40% PSC powder is recommended since it has significant nutrients and palatably accepted by sensorial panellists.